UJI DAYA HAMBAT PEWARNA ALAMI KULIT BATANG JAMBLANG (Syzygium cumini) TERHADAP BAKTERI Escherichia coli, Staphylococcus aureus DAN JAMUR Aspergilus niger - Febriana Bani Utang; Anggreini D.N Rupidara; Alan Ch Sabuna (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
ABSTRACTJamblang (Syzygium cumini) belongs to the family of the guava tribe which has benefits as a food ingredient as well as herbal medicines. Jamblang bark produces tanners (tannins) to color the nets. The purpose of this study was to determine the inhibition of natural dyes of jamblang (Syzygium cumini) bark against Escherichia coli, Staphylococcus aureus, and Aspergillus niger fungi. The method used in this study wis an experimental method, which consists of 3 treatments of natual dyes of the bark cuminis where 40%, 60%, and 80% consentrations and 3 replicates. Data of the inhibitory activity where tested using paper disk method and was analyzed statistically using ANOVA test with SPSS 16.0. statistic aplication. The natural dyes from each concentration showed a inhibitoryactivity against E. coli, S. aureus, and A. niger. The effective concentration of inhibitory activity in E. Coli was 60%, natural dyes category zonas 4.0 mm or weak inhibitory activity The effective concentration of inhibitory activity in S. aureus was 40%, natural dyes category zonas was 7.0 mm or moderateinhibitory activity. The effective concentration of inhibitory activity in A. Niger was 80% natural dyes category zonas was 4.0 mm or weak inhibitory activity.Kaywords :Antibacterial test,Jamblang (Syzygiumcumini) bark, natural coloring Escherichia coli, Staphylococcus aureus, Aspergillus niger.